Hepatitis E 3ra Genotype Infection in People Living With HIV in Spain - Rivero-Juarez, Antonio; Frias, Mario; Lopez-Lopez, Pedro; Berenguer, Juan; García, Federico; Macias, Juan; Alcaraz, Begoña; Castro-Iglesias, Angeles; Caballero-Gomez, Javier; Rivero, Antonio (Frontiers in Microbiology, 2020)
Background: The objective of our study was to assess the prevalence and incidence of HEV in people living with HIV (PLWH) in a Spanish national cohort. Methods: Retrospective longitudinal study including PLWH recruited in the cohort of adult HIV-infected patients of the AIDS Research Network in follow-up at 28 Spanish hospitals with available serum samples in 2014 and 2015. All samples were tested for HEV IgG, IgM and RNA. Samples with detectable HEV viral loads were genotyped. Prevalence and incidence of HEV infection were calculated. Results: The study sample comprised 845 PLWH. At baseline, 101 patients were positive for HEV IgG antibodies (11.9%), none had HEV IgM antibodies, and 2 presented detectable HEV RNA (0.23%). Forty-two seroconverted for IgG, supposing a cumulative incidence of 5.7%. One subject was positive for IgM (0.13%), and 2 showed detectable HEV RNA (0.27%). One case was infected by the emergent HEV genotype 3ra. Conclusions: Our study identifies one case of HEV 3ra genotype infection, the main host of which is rabbit, showing a potential zoonotic role of this emerging genotype in Spain.